11.3k views
0 votes
Find the function h(x) = f(x) ∘ g(x) if f(x) = x(2 - x) and g(x) = 3x.

h(x) = 0
h(x) = -32x
h(x) = 2(32x)
h(x) = 3x(2 - 3x)

User Mike Polen
by
6.0k points

2 Answers

4 votes
Did you write the problem down correctly? Because it looks to me like the answer should be h(x) = 32x.
User Daniel Saad
by
6.8k points
2 votes

Answer: h(x) = 3x(2 - 3x)

Explanation:

Here the given functions are,


f(x) = x(2-x)


g(x) = 3x


h(x) = f(x) \circ g(x) = (f\circ g)(x) = f[g(x)]


= f( 3x )


= (3x)[2-(3x)]


= 3x(2-3x)

Hence,


h(x) = 3x(2-3x)

Fourth option is correct.

User Chithambara Kumar
by
5.5k points